A Study to Know Self-Care Practice among Diabetic Patients Residing At Urban Slum Area of Asarwa, Ahmedabad - Patel, Vaishali C; Patel, Hely B; Shah, Chintul (National Journal of Community Medicine, 2020)
Background: Self-care of diabetes is essential for control of disease and improvement of quality of patient's life. The study was conducted to explore self-care practice of diabetic patients. Objectives: The Present study was conducted to determine the self-care practice and related factors among diabetes patients and to find out association between Glycaemic control and self-care practice. Methods: A Community based cross-sectional study was conducted by doing house to house survey. Total 120 samples who were already diagnosed taken from urban slum of asarwa, Ahmedabad. A Pre-tested structured questionnaire was adopted from Summary of Diabetes Self-Care Activities(SDSCA) and Morisky Medication Adherence Scale. Data was entered and analysed in Microsoft Excel. Results: Out of 120 patients, 63 were male and 57 were female. Majority of respondent between the age group of 45-60 years(49.17%). Half of the patients consulting from civil hospital. 68(56.7%) of respondents had good glycaemic control. Self-care practice were positively associated with achieved glycaemic control. Conclusion: As evidenced by the study, patients who were regularly involved in self-care practices have achieved better glycaemic control.